2018
DOI: 10.1080/2162402x.2018.1528411
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of the efficacy of adjuvant CIK cell therapy in epithelial ovarian cancer patients who received postoperative chemotherapy

Abstract: Cytokine-induced killer (CIK) cells are demonstrated to possess potent cytolytic effect against ovarian cancer cells in vitro and in vivo. However, the clinical efficacy of maintenance therapy of CIK cells in patients with epithelial ovarian cancer (EOC) after first-line treatment remains unclear. This retrospective study included 646 cases of postoperative EOC patients, 72 of which received chemotherapy and sequential immunotherapy (CIT group), and 574 of which received only chemotherapy (Control group). Pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 47 publications
0
23
0
Order By: Relevance
“…There are signals that CIKs could be useful in the adjuvant setting, but further evidences are needed [70].…”
Section: Combination Therapiesmentioning
confidence: 99%
“…There are signals that CIKs could be useful in the adjuvant setting, but further evidences are needed [70].…”
Section: Combination Therapiesmentioning
confidence: 99%
“…12 Among them, CIK cells, which have several characters of rapid proliferation, strong MHC-unrestricted cytolytic activity against a broad range of tumor cells, and minimal toxicity, 13,14 may be an alternative immunotherapeutic strategy for CRC patients. 12 Our and others previous clinical studies also observed the safety and efficacy of CIK cell treatment for several kinds of solid cancers, [15][16][17][18][19] including CRC. 20,21 However, to our knowledge, only one study had reported the role of CIK cell immunotherapy in the adjuvant therapeutic periods of CRC after radical surgery, and their results were limited by small sample size with only 21 patients receiving CIK cell treatment.…”
Section: Introductionmentioning
confidence: 70%
“…Early evidence from clinical trials support the feasibility and safety profile of CIK immunotherapy, with initial signs of activity and positive impact on survival outcomes in multiple solid tumors, including ovarian cancer either in advanced 31,34,38,42,[59][60][61] or even adjuvant or post-chemotherapy maintenance settings 62 .…”
Section: Discussionmentioning
confidence: 99%